2011
DOI: 10.1016/j.neuropsychologia.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal alexia: Neuropsychological mechanisms and implications for treatment

Abstract: Letter-by-letter (LBL) reading is the phenomenon whereby individuals with acquired alexia decode words by sequential identification of component letters. In cases where letter recognition or letter naming is impaired, however, a LBL reading approach is obviated, resulting in a nearly complete inability to read, or global alexia. In some such cases, a treatment strategy wherein letter tracing is used to provide tactile and/or kinesthetic input has resulted in improved letter identification. In this study, a kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In usual kinesthetic reading, a patient watches their finger while tracing a letter or character and obtains some benefits from the action, which does not contradict previous and current findings that visual feedback of finger movements is important for the facilitative effect of finger writing (Itaguchi et al, 2015(Itaguchi et al, , 2017. While the literature has focused on kinesthetic information related to language as an underlying mechanism of finger action helping patients with pure alexia while reading (Kashiwagi & Kashiwagi, 1989;Kim et al, 2011;Lott et al, 1994;Potagas et al, 2017;Seki et al, 1995), the present results suggest that the visual feedback of the movements might play a certain role in kinesthetic reading. Many studies have suggested that the impact of current visual feedback is so strong that it could invoke automatic motor action (e.g., Brass et al, 2001;Fadiga et al, 1995;Itaguchi & Kaneko, 2018) and alter the sensorimotor coordination established throughout one's life (e.g., Krakauer, 2009).…”
Section: Language Dysfunctions and Finger Movementssupporting
confidence: 58%
See 2 more Smart Citations
“…In usual kinesthetic reading, a patient watches their finger while tracing a letter or character and obtains some benefits from the action, which does not contradict previous and current findings that visual feedback of finger movements is important for the facilitative effect of finger writing (Itaguchi et al, 2015(Itaguchi et al, , 2017. While the literature has focused on kinesthetic information related to language as an underlying mechanism of finger action helping patients with pure alexia while reading (Kashiwagi & Kashiwagi, 1989;Kim et al, 2011;Lott et al, 1994;Potagas et al, 2017;Seki et al, 1995), the present results suggest that the visual feedback of the movements might play a certain role in kinesthetic reading. Many studies have suggested that the impact of current visual feedback is so strong that it could invoke automatic motor action (e.g., Brass et al, 2001;Fadiga et al, 1995;Itaguchi & Kaneko, 2018) and alter the sensorimotor coordination established throughout one's life (e.g., Krakauer, 2009).…”
Section: Language Dysfunctions and Finger Movementssupporting
confidence: 58%
“…Researching the underlying mechanism of finger movements executed intentionally or unintentionally in daily life may have many applications. Trace reading is effective in rehabilitation of patients with alexia (Kashiwagi & Kashiwagi, 1989;Kim et al, 2011;Seki et al, 1995). Seki et al (1995) showed that after a long and intensive practice of kinesthetic reading, a patient with alexia improved his reading and showed generalization to unpracticed characters, even when they were presented very briefly using a tachistoscope (200 ms) that did not allow the patient to trace them, indicating that tracing movements can be internalized.…”
Section: Language Dysfunctions and Finger Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive battery is used not only to assess acquired deficits [30,31] but also to detect more subtle developmental language deficits such as developmental dyslexia [32,33].…”
Section: Neuropsychologymentioning
confidence: 99%
“…Our hypothesis is that the subtypes of memory impairment that result will preferentially respond to specific memory interventions, a notion that is also being addressed in the aphasia treatment literature (Kim et al, 2011). To this end, an emerging method for treating neurologically-induced memory impairment is non-invasive brain stimulation (NIBS), including transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS).…”
Section: Implications For Memory Rehabilitationmentioning
confidence: 99%